TRADISI MEGIBUNG DI DESA AWANG MADYA KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT PERSFEKTIF TEOLOGI SOSIAL - Ida Made Windya (Jnanasiddhanta : Jurnal Teologi Hindu, 2023)
The tradition of megibung (eating together) has existed since the Karangasem kingdom in Lombok under the leadership of I Gusti Anglurah Ketut Karagasem. This tradition is still carried out in the community, usually related to the implementation of the pañca yajña, but lately it has rarely been carried out because there has been a shift with the buffet system which is considered more economical. Apart from being efficient, this is due to the lack of understanding of the younger generation about the meaning contained in the megibung tradition. In fact, the megibung tradition has a social and theological significances. Therefore the author tries to examine the megibung tradition from the perspective of social theology, namely a critical study of socio religious activities. The data obtained through observation, interviews and documentation will be analyzed using a qualitative descriptive method. The research results will be useful for the younger generation of Hindus in Lombok to understand the meaning of the megibung tradition, so that the megibung tradition can be maintained. Keywords: Magibung Tradition, Social Theology.